A Study of the Bacterial Population Fluctuations During Poultry Processing - Yaziz, Mohammad Ismail; Awang, Rahmat (1985)
The microbial assessment of skin-washed water samples taken from 39 poultry carcasses and the wash water from a poultry processing unit revealed cumulative increases z"n the number of microflora at each stage of processing. A comparison of the bacterial population densities on the skin at the' start and at the end of processing showed that the levels of E. coli and coli forms increased by 231.1% and 263.1% respectively whereas the Salmonella concentrations decreased by about 9%. A positive correlation was obtained between the occurrence of bacterz"a and parameters such as wash water pH and temperature, and suspended solids concentration. An examination of the storage tank effluent which was used to store the poultry carcasses pri"or to packaging showed that E. coli and Salmonella were able to thrive in the liquid. During the 4 h incubation period, the levels of both organisms decined rapidly during the initial half hour, but quickly became adapted and multipUed z"n the subsequent hours. The implications of both, the field and laboratory studies are discussed with a view of reducing the level of contamination during processing.